Thermodynamic Studies of Bovine Serum Albumin (BSA) Adsorption on Nylon Membrane - Ideris, N.; M. Roslan, A. (International Journal of Engineering and Technology, 2019)
The aim of this study was to investigate the nylon membraneâ€™s characteristics and thermodynamic aspects for adsorption of Bovine Serum Albumin (BSA) as a model protein on nylon membrane.Â The morphology characteristics analyzed by FESEM and wetting and weighting technique showed the nylon membrane possessed micro-pore size (0.159Â±0.039 Âµm) with high porosity (74.2820Â±0.0411 %) respectively.Â Thermodynamic studies indicated that the adsorption reaction was endothermic with positive value of standard enthalpy (âˆ†rHÎ¸ = 107.7 kJ/mole) and dominated by chemical adsorption.Â The results were supported with the analysis of functional groups of the nylon membrane with FTIR-ATR.Â Bands corresponding to the NH bonds stretching were generally detected in the 3500-3100 cm-1 range.Â The existence of C=O stretching vibration of carbonyl group was further confirmed with the observation of peak at 1632. 42 cm-1.Â The water contact angle analysis showed the hydrophilicity nature of nylon membrane with contact angle of 55.6Â°.Â These findings are expected to be used in the modification of nylon membrane for an optimum adsorption of protein. Â Â